The 2018 Indicators on the Governance of Sector Regulators - Part of the Product Market Regulation (PMR) Survey - Casullo, Lorenzo (OECD Publishing, 2019)
Complementing the Product Market Regulation (PMR) survey, the Indicators on the Governance of Sector Regulators map the regulatory arrangements of 130 regulators across 38 countries and five network sectors: energy, e-communications, rail and air transport, and water. The indicators are structured along three components: independence, accountability and scope of action. For the 2018 update, the OECD Secretariat and delegates of the Network of Economic Regulators (NER) revised the structure and content of the survey based on new best practice principles, guidance documents and the growing body of work of the NER on the performance of regulators. The analysis shows that, while the governance arrangements of regulators vary considerably across countries and sectors, some key trends and correlations can be observed. These insights can support countries and regulators wishing to benchmark their governance practices and reform their governance arrangements
Keywords: Economics